ANALISIS MANAJEMEN LABA PADA PERUSAHAAN DI SEKTOR INDUSTRI FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2016 - Runturambi, Irene V.; Pontoh, Winston; Gerungai, Natalia T. (Universitas Sam Ratulangi, 2017)
Earnings management becomes an interesting topic of discussion. One of the thinking that as long as done in accordance with Indonesian Financial Accounting Standards it is difficult to say as earnings management. However, accountants tend to use accounting treatment to meet certain interests. The purpose of this study is to determine whether there is earnings management in companies in the Food and Beverages Industry Sector listed on the Indonesia Stock Exchange. The data used in this study is secondary data derived from the financial statements of companies listed on the Indonesia Stock Exchange in 2015-2016. The results showed that almost all companies that become the object of research to did earnings management, either by lowering or increasing the company's profit.Keywords: Earnings Management